Meditation in the Green Labyrinth - Marina Tkacheva (Проект Байкал, 2018)
The article presents the idea of Etretat Gardens and the significance of plein-air sculpture in development of a new space. It describes “Meditation” sculpture by Dashi Namdakov located in the green labyrinth. Its peculiar arrangement in the landscape of the labyrinth is featured.